The connection between environmental attitude–behavior gap and other individual inconsistencies: a call for strengthening self-control. Issue 2 (3rd April 2017) - Redondo, Ignacio; Puelles, María
ABSTRACT: What is going on with environmental education, which is currently unable to promote pro-environmental behaviors as effectively as it promotes pro-environmental attitudes? A tentative answer is that the environmental attitude–behavior gap observed in some individuals is just one manifestation of their lack of self-control for maintaining consistency in many life spheres. In the absence of prior empirical evidence, intuition suggests that the environmental attitude–behavior gap does not appear isolated but rather interconnected to other individual inconsistencies, while a rational approach suggests that self-control (i.e. capacity to perform consistent actions) plays an important role in explaining the environmental attitude–behavior gap within the framework of the theory of planned behavior. Using data collected in Spain, we found that four individual inconsistencies (concerning fast food, alcoholic beverages, pre-cooked meals, and diet products) made an important contribution to the explanation of the environmental attitude–behavior gap, revealing a remarkable connection between personal and environmental health care. These findings suggest the importance of focusing education efforts on strengthening students' self-control in order to make them more capable of being consistent in all life endeavors.